Efficacy of high-intensity focused ultrasound-assisted hepatic resection (HIFU-AR) on blood loss reduction in patients with liver metastases requiring hepatectomy: study protocol for a randomized controlled trial. Issue 1 (December 2017) - Dupré, Aurélien; Pérol, David; Blanc, Ellen; Peyrat, Patrice; Basso, Valéria; Chen, Yao; Vincenot, Jérémy; Kocot, Anthony; Melodelima, David; Rivoire, Michel
Abstract Background Liver resection is the only potentially curative treatment for colorectal liver metastases (LM). It is considered a safe procedure, but is often associated with blood loss during liver transection. Blood transfusions are frequently needed, but they are associated with increased morbidity and risk of recurrence. Many surgical devices have been developed to decrease blood loss. However, none of them has proven superior to the standard crushing technique. We developed a new, powerful intra-operative high-intensity focused ultrasound (HIFU) transducer which destroys tissue by coagulative necrosis. We aim to evaluate whether HIFU-assisted liver resection (HIFU-AR) results in reduced blood loss. Methods This is a prospective, single-centre, randomized (1:1 ratio), comparative, open-label phase II study. Patients with LM requiring a hepatectomy for ≥ 2 segments will be included. Patients with cirrhosis or sinusoidal obstruction syndrome with portal hypertension will be excluded. The primary endpoint is normalized blood loss in millilitres per square centimetre of liver section plane. Secondary endpoints are: total blood loss, transection time, transection time per square centimetre of liver area, haemostasis time, clip density on the liver section area, rate and duration of the Pringle manœuvre, rate of patients needing a blood transfusion, length of hospital stay, morbidity, patients with positive resection margin, and local recurrence. Assuming a blood loss of 7.6 ± 3.7 mL/cm2 among controls, the study will have 85% power to detect a twofold decrease of blood loss in the experimental arm, using a Wilcoxon (Mann-Whitney) rank-sum test with a 0.05 two-sided significance level. Twenty-one randomized patients per arm are required. Considering the risk of contraindications at surgery, up to eight patients may be enrolled in addition to the 42 planned, with an enrolment period of 24 months. Randomization will be stratified by surgeon. Discussion We previously demonstrated the safety and efficacy of intra-operative HIFU in patients operated on for LM. We also demonstrated the efficacy of HIFU-AR in a preclinical study. Participants in the HIFU-AR group of this randomized trial can expect to benefit from reduced blood loss and decreased ischemia of liver parenchyma. Trial registration Clinicaltrial.gov, NCT02728167 . Registered on 22 March 2016.